Dependency of Contact Angle on Water Content and Drying Time in the Moisture Range Below Wilting Point. Issue 2 (13th March 2015) - Steyer, Ruth; Peters, Andre
Abstract : Many researchers have found an arc‐shaped curve for the apparent contact angle α vs. the equilibrium water content θ, with the highest values for α at moisture close to the wilting point and lower values under wetter and drier conditions. We hypothesized that measured α(θ) relationships are not in equilibrium in the drier moisture range and that α increases with drying time after reaching constant θ. A laboratory experiment with two water‐repellent soil materials was conducted for moisture conditions from field capacity to oven dry at 40°C. The 40°C treatments were repeated with drying times of 1 h to 4 wk. Contact angles were determined using the molarity of an ethanol droplet test. Although the θ of oven‐dried samples was constant after 1 wk, α slightly decreased with time for both materials, even after 4 wk of drying. Therefore, the hypothesis that states an increasing α with drying time at constant θ should be reconsidered.